Analisis Produksi Alpukat (Persea Americana) Di Indonesia - Kambe, Irene; ., Dyanasari; Kholil, A.Yusuf (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Avocado is a fruit that has many benefits and is popular in Indonesia. Avocado production has consistently increased over the past 5 years (2019-2024) with the largest increase in production occurring from 2020 to 2021 reaching 32%. This increase indicates that avocados have good economic prospects, so that potential development efforts focused on farming are needed. Researchers are interested in conducting research with the aim of analyzing; the development and potential of avocado production in Indonesia during the period 2001-2023 and knowing what strategies need to be implemented in Indonesia in an effort to encourage the development and potential of avocados in Indonesia. The scope of this research includes data on avocado production in Indonesia during the 21st century, from 2001 to 2023 (22 years) obtained from FAOSTAT (2025). The methods and stages of data analysis used in this study consist of; First, descriptive analysis: Second, Compounded Annual Growth Rate (CAGR): Third, literature study: fourth, a scenario for increasing Indonesian avocado production was designed, compared with avocado production results in Mexico: fifth, a discussion was conducted regarding strategies that can be implemented by Indonesia to increase the competitiveness of avocado production. The results of the analysis of avocado production in Indonesia and Mexico, obtained that: The development of avocado production in Indonesia (2001-2023) over the past 22 years, overall increased. However, advances in agricultural technology and government policy support helped this sector recover and continue to grow. The average annual production growth (CAGR) is 2.46%, indicating stable growth. The potential for avocado production in Indonesia during the period (2024-2046) is estimated to increase steadily from 664,872 tons and in 2046 increase to 1,468,612 tons.